On the Physical Layer Security Peculiarities of Wireless Communications in the Presence of the Beaulieu-Xie Shadowed Fading - Aleksey S. Gvozdarev; Tatiana K. Artemova (Mathematics, 2022)
The article presents an analysis of the physical layer security of a wireless communication system functioning in the presence of multipath fading and a wiretap. Under the assumption of the equal propagation conditions (both for the legitimate receiver and the eavesdropper) described by the shadowed Beaulieu–Xie model, a closed-form expression for the secrecy outage probability was derived. The correctness of the obtained expression was numerically verified via comparison with the direct numerical integration. The truncated version of the obtained expression was analyzed for various channel parameters to establish the requirements for numerically efficient implementation (in terms of the number of summands delivering the desired precision). An in-depth study of the secrecy outage probability dependence from all the possible channel parameters for different fading scenarios was performed, including heavy fading and light fading, with and without strong dominant and multipath components. The performed research demonstrated the existence of the secrecy outage probability non-uniqueness with the respect to the average signal-to-noise ratio in the main channel and the relative distance between the legitimate and wiretap receivers.